2013
DOI: 10.1187/cbe.13-05-0090
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Clicker Discussions: Student Reasoning and the Impact of Instructional Cues

Abstract: This paper characterizes in-class discussion of clicker questions among upper-level biology majors, demonstrating that students exchanged ideas in 75% of the recorded clicker discussions, using high-quality reasoning almost 50% of the time. In addition, when cued by the instructor to use reasoning, they engaged in higher-quality discussions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
104
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(112 citation statements)
references
References 31 publications
5
104
0
3
Order By: Relevance
“…In addition, during discussions when there is disagreement, as it is the case in the some correct answer groups, those peers with the correct response (and the right reasons) mostly convince their peers to change. Knigth et al (16) by recording peer instruction activities found cooperative group construction of knowledge in a high proportion (ϳ75%) of the peer discussions. Therefore, this provides support to the idea that the benefits of collaboration are not just the consequence of knowledge transmission (one student saying the correct answer to other group members) but the result of coconstruction of new knowledge by debate and discussion.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, during discussions when there is disagreement, as it is the case in the some correct answer groups, those peers with the correct response (and the right reasons) mostly convince their peers to change. Knigth et al (16) by recording peer instruction activities found cooperative group construction of knowledge in a high proportion (ϳ75%) of the peer discussions. Therefore, this provides support to the idea that the benefits of collaboration are not just the consequence of knowledge transmission (one student saying the correct answer to other group members) but the result of coconstruction of new knowledge by debate and discussion.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Knight et al (2013) investigated peer discussions among students in an upper-division university-level biology course. Specifically, this study focused on turns of talk, coding student conversations for elements of arguments: claim, reasoning, questioning, and background (Driver et al 2000;Osborne et al 2004).…”
Section: Learning Benefits Of Peer Discussion During Clicker Questionsmentioning
confidence: 99%
“…Viktige aspekter med Peer Instruction ble likevel beholdt, ved at studentene diskuterte sine ideer og løsninger med sine medstudenter (peers) (Crouch & Mazur, 2001;Knight & Brame, 2018). Et viktig aspekt her er å presentere oppgaver som er utfordrende nok for studentene, for å lage større rom for diskusjon (Knight, Wise, & Southard, 2013;Zingaro & Porter, 2014). I denne studien var oppgavesettet som ble delt ut spesialtilpasset ut ifra hva studentene skulle laere (laeringsutbyttebeskrivelsene) og tidligere eksamensoppgaver.…”
Section: Klasserommetunclassified